Hyperpolarized carbon 13 MRI: clinical applications and future directions in oncology - Deen, SS; Rooney, C; Shinozaki, A; McGing, J; Grist, JT; Tyler, DJ; Serraro, E; Gallagher, FA (Radiological Society of North America, 2023)
Hyperpolarized carbon 13 MRI (13C MRI) is a novel imaging approach that can noninvasively probe tissue metabolism in both normal and pathologic tissues. The process of hyperpolarization increases the signal acquired by several orders of magnitude, allowing injected 13C-labeled molecules and their downstream metabolites to be imaged in vivo, thus providing real-time information on kinetics. To date, the most important reaction studied with hyperpolarized 13C MRI is exchange of the hyperpolarized 13C signal from injected [1-13C]pyruvate with the resident tissue lactate pool. Recent preclinical and human studies have shown the role of several biologic factors such as the lactate dehydrogenase enzyme, pyruvate transporter expression, and tissue hypoxia in generating the MRI signal from this reaction. Potential clinical applications of hyperpolarized 13C MRI in oncology include using metabolism to stratify tumors by grade, selecting therapeutic pathways based on tumor metabolic profiles, and detecting early treatment response through the imaging of shifts in metabolism that precede tumor structural changes. This review summarizes the foundations of hyperpolarized 13C MRI, presents key findings from human cancer studies, and explores the future clinical directions of the technique in oncology.